The Wiener-Hopf method in electromagnetics ISMB series - Zich, Rodolfo 1939-; Daniele, Vito 1942- (Edison, NJ SciTech Publishing Inc., 2014)
This monograph presents the Wiener-Hopf method in theoretical electromagnetism.
Order of authors reversed on cover.
Electronic reproduction.
Keywords: Electromagnetism -- Mathematics; Wiener-Hopf equations; Electromagnetic waves -- Diffraction -- Mathematics; Electromagnetism; Integral equations; Electronic books